Sharing the burden of adaptation financing: An assessment of the contributions of countries - Rob B. Dellink; Michel den Elzen; Harry Aiking; Emmy Bergsma (Fondazione Eni Enrico Mattei (FEEM), 2009)
Climate change may cause most harm to countries that contribute least to greenhouse gas emissions. This paper identifies deontology, solidarity and consequentialism as the principles that can serve as a basis for a fair international burden sharing scheme of adaptation costs. We translate these principles into criteria that can be applied in assigning contributions of individual countries, namely historical responsibility, equality and capacity to pay. Specific political and scientific choices are discussed, highlighting implications for international burden-sharing. Combining historical responsibility and capacity to pay seems a promising starting point for international negotiations on the design of burden-sharing schemes. From the numerical assessment, it is clear that UNFCCC Annex I countries carry the greatest burden under most scenarios, but contributions differ substantially subject to the choice of an indicator for capacity to pay. The total financial contribution by the Annex I countries could be in the range of 55-68 billion annually.
Keywords: F55; Q54; 330; Adaptation Financing; Burden-Sharing; Historical Responsibility